RELEVANSI KEGIATAN PRAKTIKUM DENGAN TEORI DAN PEMAHAMAN MAHASISWA PADA MATA KULIAH KIMIA DASAR LANJUT - Resti T Astuti (Orbital: Jurnal Pendidikan Kimia, 2020)
This study aims to describe the relevance of chemistry practicum with theory and describe students' understanding in advanced basic chemistry courses. Data collection techniques used in this study were interview guidelines, documentation consisting of lesson design, student grades, KKNI curriculum for chemical education study programs, and chemistry practicum guides. The results of the study are practicum factors that affect the rate of reaction obtained a percentage of 96.08% is very relevant to the theory of chemical kinetics. The chemical equilibrium practicum obtained a percentage of 94.12% which shows that the practicum is very relevant to acid-base equilibrium material. Acid-base titration practicum obtained 84.31% percentage which means that acid-base titration practicum was relevant to acid-base equilibrium material. Practicum of the solubility product constant obtained a percentage of 98.04% which shows the practicum is very relevant to the material of solubility equilibria. Students' understanding of practicum, namely the factors that affect the rate of reaction obtained a percentage of 97.06% with a very good category, a chemical equilibrium practicum percentage of 90.20% with a very good category. Acid-base titration practicum obtained a percentage of 96.08% with a very good category. The equilibrium practicum results obtained a percentage of 96.57% with a very good category. Students' understanding is based on grades in advanced basic chemistry courses, namely students who get A grade of 25.24%, B grade with percentage of 72.55% and D grade of 1.96%.